Mild Traumatic Brain Injury in Adolescent Mice Alters Skull Bone Properties to Influence a Subsequent Brain Impact at Adulthood: A Pilot Study - McColl, Thomas J.; Brady, Rhys D.; Shultz, Sandy R.; Lovick, Lauren; Webster, Kyria M.; Sun, Mujun; McDonald, Stuart J.; O’Brien, Terence J.; Semple, Bridgette D. (Frontiers in Neurology, 2018)
Mild traumatic brain injuries (mTBI) are common during adolescence, and limited clinical evidence suggests that a younger age at first exposure to a mTBI may lead to worse long-term outcomes. In this study, we hypothesized that a mTBI during adolescence would predispose towards poorer neurobehavioral and neuropathological outcomes after a subsequent injury at adulthood. Mice received a mild weight-drop injury (mTBI) at adolescence (postnatal day 35; P35) and/or at adulthood (P70). Mice were randomized to 6 groups: 'sham' (sham-surgery at P35 only); 'P35' (mTBI at P35 only); 'P35+sham' (mTBI at P35 + sham at P70); 'sham+P70' (sham at P35 + mTBI at P70); 'sham+sham' (sham at both P35 and P70); or 'P35+P70' (mTBI at both P35 and P70). Acute apnea and an extended righting reflex time confirmed a mTBI injury at P35 and/or P70. Cognitive, psychosocial, and sensorimotor function was assessed over one week post-injury. Injured groups performed similarly to sham controls across all tasks. Immunofluorescence staining at 1 week detected an increase in glial activation markers in Sham+P70 brains only. Strikingly, 63% of Sham+P70 mice exhibited a skull fracture at impact, compared to 13% of P35+P70 mice. Micro computed tomography of parietal skull bones found that a mTBI at P35 resulted in increased bone volume and strength, which may account for the difference in fracture incidence. In summary, a single mTBI to the adolescent mouse brain did not exacerbate the cerebral effects of a subsequent mTBI in adulthood. However, the head impact at P35 induced significant changes in skull bone structure and integrity. These novel findings support future investigation into the consequences of mTBI on skull bone.